Nuclear ecologies: art and collaboration in post-3.11 Japan - Deichert, Theresa (Visual and media histories, 2026)
This book traces the Fukushima nuclear disaster of March 2011 and how art emerged as a powerful response to the socio-political and environmental consequences. Artists turned to collaborative and ecological practices to make sense of the crisis, challenging official narratives and responding to the violence of radioactive contamination